2011
DOI: 10.2298/bah1103017j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat stress on milk production in dairy cows

Abstract: Heat stress in dairy cows is caused by a combination of environmental factors (temperature, relative humidity, solar radiation and air movement). Continual genetic selectin for greater performance results to increased sensitivity to heat stress. It was one of the reasons why lactation curve during summer has decreasing trend compared to spring in which lactation curve maintained within high levels. The trial was conducted in spring (April-May) and summer period (June-July) on total of 40 dairy cows of Holstein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…[ 48 ] reported that with increases in THI from 59.82 in the winter season to 78.53 in the summer season, HS reduced total (305 days) and daily milk yield by 39.00%, 31.40% and 29.84%, respectively. Total average milk production/cow was significantly (p<0.05) higher in spring period (42.74±4.98 L) compared to summer (39.60±5.091 L) [ 49 ]. Drop in milk production up to 50% in dairy animals might be due to reduced feed intake [ 9 ], whereas, rest could be reasons of metabolic adaptations to HS as HS response markedly alters post-absorptive carbohydrate, lipid, and protein metabolism a part of reduced feed intake [ 9 ].…”
Section: Effect Of Hs On Production and Reproduction Performance Of Dmentioning
confidence: 99%
“…[ 48 ] reported that with increases in THI from 59.82 in the winter season to 78.53 in the summer season, HS reduced total (305 days) and daily milk yield by 39.00%, 31.40% and 29.84%, respectively. Total average milk production/cow was significantly (p<0.05) higher in spring period (42.74±4.98 L) compared to summer (39.60±5.091 L) [ 49 ]. Drop in milk production up to 50% in dairy animals might be due to reduced feed intake [ 9 ], whereas, rest could be reasons of metabolic adaptations to HS as HS response markedly alters post-absorptive carbohydrate, lipid, and protein metabolism a part of reduced feed intake [ 9 ].…”
Section: Effect Of Hs On Production and Reproduction Performance Of Dmentioning
confidence: 99%
“…Increased TEM in combination with inappropriate HUM induces temperature stress dairy cows (Brouček et al, 2006), which is manifested by immediately milk production decrease as well as gradual decline after several days of exposure (West et al, 2003). Milk production and chemical composition changes of milk evoked by heat stress was confirmed also Bouraoui et al (2002), Tapki andSahin (2006), andJoksimović-Todorović et al (2011). The toleration to temperature stress is influenced by lactation phase, when this ability is the lowest in cows after calving and in the first part of lactation (Brouček et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the zone which can be described as thermal comfort zone refers to the temperature interval in which cattle is not affected by cold and hot temperatures (15). Although it changes according to breed and age, it is stated that the most appropriate environmental temperature conditions for dairy cows are [13][14][15][16][17][18] º C, 60-70% of relative humidity, moderate level solar radiation and 5-8 km/h wind speed (28). Heat stress is shaped by the combination of such environmental factors as temperature, relative humidity, solar radiation, wind speed and precipitation (6,28).…”
Section: Introductionmentioning
confidence: 99%
“…Another is Benezra's thermal comfort index, which is based on rectal temperature and respiratory rate (3). However, the Temperature Humidity Index (THI) based on temperature and relative humidity is used more commonly (8,12,14,15,18). It is reported that the indices attaching more importance to humidity should be used in humid regions; whereas, the indices which attach more importance to temperature should be used in semi-arid regions (6).…”
Section: Introductionmentioning
confidence: 99%